Mesozoic atmospheric CO 2 concentrations reconstructed from dinosaur tooth enamel - Dingsu Feng; Thomas Tütken; Eva Maria Griebeler; Daniel Herwartz; Andreas Pack (Proceedings of the National Academy of Sciences, 2025)
Air-breathing vertebrates incorporate a fraction of isotopically anomalous air O 2 in their body water. The 17 O isotope anomaly of air O 2 (expressed as Δ’ 17 O air ) is related to atmospheric CO 2 concentrations ( p CO 2 ) and gross primary production (GPP). Tooth enamel records the Δ’ 17 O of body water and can thus preserve such paleo- p CO 2 or paleo-GPP information over geological time periods. Here, we demonstrate the potential of respective reconstructions of atmospheric p CO 2 or GPP from the triple oxygen isotope composition of fossil dinosaur tooth enamel. The data from unaltered enamel samples, along with an assumed modern GPP t /GPP 0 ratio of 1 for the Mesozoic, suggest a mean Late Jurassic p CO 2 = 1,200 ± 150 ppmv and Late Cretaceous p CO 2 = 750 ± 200 ppmv. These estimates are in good agreement with other p CO 2 proxy data for the same time intervals. When utilizing a p CO 2 inferred from other proxies, tooth enamel Δ’ 17 O PO4 may also serve as a proxy for GPP. Using published p CO 2 data, we reconstructed GPP t /GPP 0 ratios with 1.20 ± 0.17 for the Late Jurassic and 2.24 ± 0.96 for the Late Cretaceous, which would imply a 20 to 120% higher GPP in the Mesozoic than today. Overall, triple oxygen isotope analysis of fossil teeth of terrestrial amniotes can provide insights into past atmospheric greenhouse gas content and global primary productivity.